Effects of face masks on performance and cardiorespiratory response in well-trained athletes - Egger, F.; Blumenauer, D.; Fischer, P.; Venhorst, A.; Kulenthiran, S.; Bewarder, Y.; Zimmer, A.; Böhm, M.; Meyer, T.; Mahfoud, F. (Clinical Research in Cardiology, 2022)
Background: During the COVID-19 pandemic, compulsory masks became an integral part of outdoor sports such as jogging in crowded areas (e.g. city parks) as well as indoor sports in gyms and sports centers. This study, therefore, aimed to investigate the effects of medical face masks on performance and cardiorespiratory parameters in athletes. Methods: In a randomized, cross-over design, 16 well-trained athletes (age 27 ± 7 years, peak oxygen consumption 56.2 ± 5.6 ml kg-1 min-1, maximum performance 5.1 ± 0.5 Watt kg-1) underwent three stepwise incremental exercise tests to exhaustion without mask (NM), with surgical mask (SM) and FFP2 mask (FFP2). Cardiorespiratory and metabolic responses were monitored by spiroergometry and blood lactate (BLa) testing throughout the tests. Results: There was a large effect of masks on performance with a significant reduction of maximum performance with SM (355 ± 41 Watt) and FFP2 (364 ± 43 Watt) compared to NM (377 ± 40 Watt), respectively (p < 0.001; Etap2 = 0.50). A large interaction effect with a reduction of both oxygen consumption (p < 0.001; Etap2 = 0.34) and minute ventilation (p < 0.001; Etap2 = 0.39) was observed. At the termination of the test with SM 11 of 16 subjects reported acute dyspnea from the suction of the wet and deformed mask. No difference in performance was observed at the individual anaerobic threshold (p = 0.90). Conclusion: Both SM and to a lesser extent FFP2 were associated with reduced maximum performance, minute ventilation, and oxygen consumption. For strenuous anaerobic exercise, an FFP2 mask may be preferred over an SM.